Heart Rate Control in Patients With Chronic Atrial Fibrillation and Heart Failure. Issue 1 (9th September 2012) - Silvet, Helme; Hawkins, Lee Ann; Jacobson, Alan K.
Abstract : ©2012 Wiley Periodicals, Inc. The goal of this study was to determine whether aggressive heart rate (HR) control in patients with both chronic atrial fibrillation (AF) and heart failure (HF) is associated with improved outcomes. HR control is one of the mainstays in management of patients with AF. However, rate control can be challenging in patients with HF. This study was designed as an interventional clinical trial, using patients with chronic AF and left ventricular systolic dysfunction with left ventricular ejection fraction ≤40% (n=20) as their own controls. Intervention consisted of increasing doses of metoprolol succinate to achieve target resting HR <70 beats per minute. Clinical data were collected at baseline and after intervention, with paired t test used to evaluate statistically significant change. After 3 months of intervention, average resting HR decreased from 94±14 beats per minute to 85±12 beats per minute. Average metoprolol succinate dose at the end of the study was 121 mg. None of the outcomes improved significantly after the intervention, including exercise tolerance (meters walked on 6‐minute walk test 326±83 vs 330±86), quality of life (Minnesota Living With Heart Failure Questionnaire score of 42.5±19 vs 38±21), and brain natriuretic peptide (242±306 pg/mL vs 279±395 pg/mL). Aggressive HR control was difficult in this group of patients with chronic AF and HF due to patient intolerance of increasing doses of β‐blockade, and not associated with improved outcomes. Further studies are needed to establish guidelines for target HR in patients with chronic AF who also have significant HF.